Bruno-3 regulates sarcomere component expression and contributes to muscle phenotypes of myotonic dystrophy type 1 - Lucie Picchio; Vincent Legagneux; Stephane Deschamps; Yoan Renaud; Sabine Chauveau; Luc Paillard; Krzysztof Jagla (The Company of Biologists, 2018)
Steinert disease, or myotonic dystrophy type 1 (DM1), is a multisystemic disorder caused by toxic noncoding CUG repeat transcripts, leading to altered levels of two RNA binding factors, MBNL1 and CELF1. The contribution of CELF1 to DM1 phenotypes is controversial. Here, we show that the Drosophila CELF1 family member, Bru-3, contributes to pathogenic muscle defects observed in a Drosophila model of DM1. Bru-3 displays predominantly cytoplasmic expression in muscles and its muscle-specific overexpression causes a range of phenotypes also observed in the fly DM1 model, including affected motility, fiber splitting, reduced myofiber length and altered myoblast fusion. Interestingly, comparative genome-wide transcriptomic analyses revealed that Bru-3 negatively regulates levels of mRNAs encoding a set of sarcomere components, including Actn transcripts. Conversely, it acts as a positive regulator of Actn translation. As CELF1 displays predominantly cytoplasmic expression in differentiating C2C12 myotubes and binds to Actn mRNA, we hypothesize that it might exert analogous functions in vertebrate muscles. Altogether, we propose that cytoplasmic Bru-3 contributes to DM1 pathogenesis in a Drosophila model by regulating sarcomeric transcripts and protein levels.